Top 10 research achievements of traditional Chinese medicine in 2023 (Science of Traditional Chinese Medicine)
Abstract. In order to fulfill the requirements of the 20th National Congress of the Communist Party of China and the Opinions on Promoting the Inheritance, Innovation and Development of Traditional Chinese Medicine, regularly summarize the research achievements of traditional Chinese medicine (TCM), present the academic progress of TCM dynamically, and give full play to the leadership of academic groups in research, the China Association of Chinese Medicine organized the selection of the top 10 academic achievements of TCM in 2023. The selection work adhered to the “4 orientations”; eliminated the “4 only”; highlighted the solution of clinical problems and scientific questions, the development of the industry, and the exploratory, forward-looking, innovative, and breakthrough research; and focused on new laws, new discoveries, new methods, new products, and new theories in the basic research and applied basic research of TCM. After dynamic collection, preliminary examination, review, and final judgment, the top 10 academic achievements of TCM in 2023 were determined. First, breakthroughs have been achieved in the treatment of ST-segment elevation myocardial infarction by Tongxinluo. Second, evidence has been gained regarding the efficacy of acupuncture in treating chronic spontaneous urticaria and vomiting in pregnancy. Third, evidence has been gained regarding the improvement of neurological function outcomes by Xuesaitong soft capsules in treating patients with ischemic stroke. Fourth, the mechanisms of Huashi Baidu Powder and Pien Tze Huang in clinical treatment have been revealed. Fifth, the pharmacodynamic mechanisms of astragaloside and capsaicin have been revealed for the first time. Sixth, new technologies represented by spatial metabolomics assist in elucidating the material basis of the complex systems of TCM. Seventh, network medicine framework reveals the generic mechanism underlying the effectiveness of TCM treatment based on syndrome differentiation. Eighth, a comprehensive platform for multidimensional nucleic acid data of TCM promotes data sharing in molecular pharmacognosy. Ninth, multiprocess transfer and information fusion provide solutions for digital manufacturing of big honeyed pills. Tenth, the scientific system of TCM regulatory science has been preliminarily built and applied.